To Determine the Relation of Oral Health Status and Selected Correlates among Students Attending Various Universities of Lahore, Pakistan - Shariq Ali Khan, Sahrish Jabeen, Adeel Tuasene, Shehryar Awan, Anila Errum, Ahmed Mujtaba, Rizwan Saeed (Pakistan Journal of Medical & Health Sciences, 2022)
When health is concerned, we must pay attention to all the parts of human body specially the oral cavity. Oral cavity is the gateway of many diseases in human body. There are many reasons for this spread, one of the reason is food. In this regard, the health care of oral cavity is the most essential constituent of general health and wellbeing of any individual. Low health literacy is the cause of all oral health related issues. Health education creates awareness among people that for a better life style it is equally important to seek and get proper health care as obtaining of other necessities of life. The grave consequences of low health literacy have been reviewed many times. This study was conducted on the young adults of Pakistan currently enrolled at different universities and colleges of Lahore, Pakistan. The main objective of the study was to know about the oral health literacy level of the participants and then find out its relationship with their oral health status which was find out after clinical examination. The purpose of the study was to get an idea about the health outcome of the most efficient group of population. Sample for this study will be collected in 2 steps. Step 1 was conducted by doing the clinical examination of the participants in order to assess oral health index. Step 2 was conducted by doing the short interviews of each participant in order to assess oral health literacy of the participants. All the data was complied. The results of REALD 30 word list from all 400 participants were analyzed and the average score was calculated. The average score came out to be 22.46. With this study, it was proved that education plays a significant role in improving oral health status. Further studies can be conducted to help spreading awareness and basic education related programs for uneducated people.